Experimental investigation of ignition timing on the performance and emission characteristics of a crank-rocker engine - Mohammed, S.E. (MechAero Found. for Techn. Res. and Educ. Excellence, 2018)
The effects of varying the ignition timing on the performance and emissions characteristics of a crank-rocker engine were experimentally investigated. Experiments were carried out at five different ignition timings of 6.5°, 8.5°, 10.5°, 12.5°and 14.5° CA BTDC at engine speed of 2000rpm and wide open throttle position. Performance data such as brake torque, brake power, brake specific fuel consumption and brake thermal efficiency were calculated. Engine exhaust gas emission such as CO, CO2, HC and NOx have also been measured. The results showed that at 10.5° CA (BTDC) ignition timing, the crank-rocker engine produce maximum brake torque, brake power, BTE and minimum value for the BSFC. In general, CO and HC emissions decreased while CO2 and NOx emissions increased with ignition timing advance. The findings in this paper are useful for researchers and engine developers in understanding the trade-offs and physical limitations of crank-rocker engine designs. © 2018.